YC‐1 inhibits proliferation of breast cancer cells by down‐regulating EZH2 expression via activation of c‐Cbl and ERK. (25th July 2014) - Chang, Ling‐Chu; Lin, Hui‐Yi; Tsai, Meng‐Tung; Chou, Ruey‐Hwang; Lee, Fang‐Yu; Teng, Che‐Ming; Hsieh, Min‐Tsang; Hung, Hsin‐Yi; Huang, Li‐Jiau; Yu, Yung‐Luen; Kuo, Sheng‐Chu
<x xml:space="preserve">Abstract</x> Background and Purpose YC‐1 exhibits potent anticancer activity via numerous actions in many cancer cell lines. Hence, we investigated the in vivo antitumour efficacy of YC‐1 in an MDA‐MB‐468 xenograft model and elucidated the mechanism of down‐regulation of enhancer of zeste homology 2 (EZH2) by YC‐1 in breast cancer cells. Experimental Approach In YC–1‐treated breast cancer cells and tumour specimens from YC–1‐treated MDA‐MB‐468 xenografts, EZH2 expression was analysed by Western blotting. Pharmacological inhibitors and short hairpin RNA‐mediated knockdown were applied to identify possible signalling pathways involved in EZH2 down‐regulation by YC‐1. Key Results YC‐1 reduced the viability of breast cancer cells and tumour growth in MDA‐MB‐468 xenografts. In breast cancer cells, YC‐1 down‐regulated EZH2 expression in a concentration‐ and time‐dependent manner. Depletion of EZH2 reduced the proliferation and susceptibility of breast cancer cells to YC–1‐induced apoptosis. EZH2 expression was suppressed in tumour specimens from YC–1‐treated MDA‐MB‐468 xenograft mice. YC‐1 enhanced both the degradation rate and ubiquitination of EZH2. The down‐regulation of EZH2 by YC‐1 was associated with activation of PKA and Src–Raf–ERK‐mediated signalling pathways. Furthermore, depletion of Casitas B‐lineage lymphoma (c‐Cbl), an E3 ubiquitin ligase, abolished YC–1‐induced apoptosis and suppression of EZH2. YC‐1 rapidly activated c‐Cbl to induce signalling associated with ERK and EZH2. Conclusion and Implications We discovered that YC‐1 induces apoptosis and inhibits tumour growth of breast cancer cells via down‐regulation of EZH2 by activating c‐Cbl and ERK. These data suggest that YC‐1 is a potential anticancer drug candidate for triple‐negative breast cancer.